Neonatal Thyroid-Stimulating Hormone Concentrations in Belgium: A Useful Indicator for Detecting Mild Iodine Deficiency? - Vandevijvere, Stefanie (Public Library of Science, 2012)
It has been proposed that neonatal thyroid-stimulating hormone (TSH) concentrations are a good indicator of iodine deficiency in the population. A frequency of neonatal TSH concentrations above 5 mU/L below 3% has been proposed as the threshold indicating iodine sufficiency. The objective of the present study was to evaluate feasibility and usefulness of nation-wide neonatal TSH concentration screening results to assess iodine status in Belgium. All newborns born in Belgium during the period 2009–2011 (n = 377713) were included in the study, except those suffering from congenital hypothyroidism and premature neonates. The frequency of neonatal TSH concentrations above 5 mU/L from 2009 to 2011 in Belgium fluctuated between 2.6 and 3.3% in the centres using the same TSH assay. There was a significant inverse association between neonatal TSH level and birth weight. The longer the duration between birth and screening, the lower the TSH level. Neonatal TSH levels were significantly lower in winter than in spring or autumn and significantly lower in spring and summer than in autumn while significantly higher in spring compared to summer. In conclusion, despite that pregnant women in Belgium are mildly iodine deficient, the frequency of neonatal TSH concentrations above 5 mU/L was very low, suggesting that the neonatal TSH threshold proposed for detecting iodine deficiency needs to be re-evaluated. Although neonatal TSH is useful to detect severe iodine deficiency, it should not be recommended presently for the evaluation of iodine status in mildly iodine deficient regions.